Nickel-Catalyzed Reductive Cross-Coupling of Benzylic Sulfonium Salts with Aryl Iodides - Wang, Wei; Yao, Ken; Wu, Fan (Synlett, 2022)
A nickel-catalyzed cross-electrophile coupling of benzylic sulfonium salts with aryl iodides has been developed, providing direct access to diarylalkanes from readily available and stable coupling partners. Preliminary mechanistic studies suggest that the C–S bond cleavage proceeds through a single-electron transfer process to generate a benzylic radical.
Keywords: nickel catalysis; cross-coupling; arylation; diarylalkanes; sulfonium salts; aryl iodides